PENGGUNAAN ALAT PERMAINAN EDUKASI STIK ES KRIM PINTAR DALAM MENUMBUHKAN KEMAMPUAN KEAKSARAAN ANAK USIA DINI - Sariasih, Ni Luh Sariasih; Sedana Suci, I Gede; Suardika, I Komang (Pratama Widya: Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood is the next generation of the nation that needs serious attention. This potential needs to be stimulated and facilitated in order to develop optimally. Media is an important aspect to support children's early literacy skills. This media is a simple learning media by combining the alphabet (a-z) which is made on origami paper and underneath there are ice cream sticks. This study used three theories consisting of behavioristic theory, constructive theory, and maturationist theory. This research uses classroom action research. The results obtained depicted an increase in learning mastery as much as 14 or 93.3% of students had met the minimum completeness criteria. In the observation of Cycle II, this research has reached the criteria of success indicators that have been set, namely 80% of the total number of students. The impact of using smart ice cream stick educational game tools in growing literacy skills in Besan Village Kindergarten is that children recognize letters well (pre-writing program), children can learn while playing, help stimulate children's fine motor skills, foster a spirit of togetherness among children, improve children's ability to listen and increase children's vocabulary.